2017
DOI: 10.1038/s41598-017-12364-w
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free synthesis of functional antibodies using a coupled in vitro transcription-translation system based on CHO cell lysates

Abstract: Antibodies are indispensable tools for basic research as well as diagnostic and therapeutic applications. Consequently, the development of alternative manufacturing strategies which circumvent the hurdles connected to conventional antibody production technologies is of enormous interest. To address this issue, we demonstrate the synthesis of complex antibody formats, in particular immunoglobulin G (IgG) and single-chain variable fragment Fc fusion (scFv-Fc), in a microsome-containing cell-free system based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 60 publications
(62 reference statements)
2
60
0
Order By: Relevance
“…Most progress has occurred in CFE systems generated from Escherichia coli strains engineered for protein production, largely due to the bacterium's well-characterized genetics and metabolism [1]. However, there has been recent progress in adapting CFE protocols to make lysates from eukaryotic and non-model organisms, including yeast [43,44], Gram-positive bacteria [45,46], plants [47,48], and mammalian cells [49][50][51]. CFE technology is therefore now at the point of expanding beyond specialist laboratories and becoming a major toolbox throughout synthetic biology research, application, and recently, education [34,52,53].…”
Section: Introductionmentioning
confidence: 99%
“…Most progress has occurred in CFE systems generated from Escherichia coli strains engineered for protein production, largely due to the bacterium's well-characterized genetics and metabolism [1]. However, there has been recent progress in adapting CFE protocols to make lysates from eukaryotic and non-model organisms, including yeast [43,44], Gram-positive bacteria [45,46], plants [47,48], and mammalian cells [49][50][51]. CFE technology is therefore now at the point of expanding beyond specialist laboratories and becoming a major toolbox throughout synthetic biology research, application, and recently, education [34,52,53].…”
Section: Introductionmentioning
confidence: 99%
“…In cell-free systems, core glycosylation can be achieved by supplementing extracts with microsomal fractions (Walter & Blobel, 1983). An insect cell-free system offers core protein glycosylation without the need for supplementing the microsomes in the reaction (Stech et al, 2014;Tarui et al, 2001). Recent studies reported the expression of recombinant erythropoietin using microsomes in CHO cell-free system showing the presence of glycosylated and unglycosylated forms (Brodel et al, 2013(Brodel et al, , 2014(Brodel et al, , 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators (Table 1) have used the E. coli CFPS, insect CFPS and CHO CFPS systems for the expression of human EPO (Ahn, Choi, & Kim, 2005;Ahn, Hwang, Lee, Choi, & Kim, 2007;Brodel, Sonnabend, & Kubick, 2014;Brodel, Wustenhagen, & Kubick, 2015;Stech et al, 2014). However, no further optimization studies were reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of anti-spliced leader oligonucleotide to L. tarentolae cell extracts suppressed the translation of endogenous L. tarentolae mRNAs, thus increasing the translation efficiency of exogenously supplied mRNA [65]. Using the ER-specific signal sequence of honeybee melittin (melittin signal peptide) instead of the native signal peptide increased the translocation of synthesized proteins such as WNT proteins, single-chain antibody variable fragments, and the hTLR9-ectodomain into microsomes in the case of Sf21 and CHO-based CF systems [18,59,74,75].…”
Section: Gene Designmentioning
confidence: 99%